An analysis of the educational material needs for children with special needs: perspectives from students and tutors of the preservice teacher program at Universitas Terbuka - Monika Handayani; Uliya Khoirun Nisa; Andayani; Rifat Shafwatul Anam; Ika Tri Yuanika (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study investigates the expectations of students and tutors in the Primary School Teacher Education (PGSD) program at Universitas Terbuka regarding instructional resources for the Special Needs Children Education (ABK) course. A needs analysis was conducted through surveys and interviews to inform the development of adaptive and inclusive materials aligned with the PGSD curriculum. Results show that 88.77% of students and 84.5% of tutors emphasized the importance of inclusive education in ABK materials. Moreover, 78.56% of students and 81% of tutors agreed on updating previous resources. In terms of accessibility, 90% of students and 66.6% of tutors considered earlier materials conceptually rich. The visual presentation remained appealing to 55% of students and 61.9% of tutors, and grammar was deemed clear by 66.3% of students and 57.1% of tutors. Divergent views emerged on interactivity: 40.8% of students found older resources less engaging, while 61.9% of tutors disagreed. Interviews highlighted the need for materials based on Universal Design for Learning (UDL), integrating technology, and adaptable to diverse student needs. Thus, interactive multimedia-based resources are recommended to meet both academic and practical demands of PGSD students.